Understanding Omnichannel Shopping Behaviors: Incorporating Channel Integration into The Theory of Reasoned Action - Jay Sang Ryu; Sally Fortenberry; Patricia Warrington (Journal of Consumer Sciences, 2023)
Young consumers prefer to switch shopping channels freely for optimal shopping results and experiences. To meet these changing needs, retailers have begun implementing an omnichannel retail strategy that integrates their various shopping channels to create a consistent and seamless shopping environment. Thus, this study examines the effect of young consumers' perceptions of the retailer's channel consistency and seamlessness on their attitudes, intentions, and behaviors in the omnichannel retailing context. We incorporated the concept of channel consistency and seamlessness into the Theory of Reasoned Action to address the study objective. A consumer research firm was hired to recruit millennials and Gen Z consumers, and online surveys took place in the U.S. in 2019, and 430 usable surveys were analyzed with SPSS and AMOS. The results confirmed that consumers’ perception of channel seamlessness positively impacted their attitudes toward omnichannel shopping. Furthermore, these attitudes and subjective norms increased their intentions, leading to engagement in omnichannel shopping. The findings suggest that retailers must create smooth and uninterrupted shopping experiences across channels and proactively manage social components to create a customer’s omnichannel shopping experience